Autism : educational and therapeutic approaches - Kalyva, Efrosini (Los Angeles : SAGE, 2011)
There are a number of different approaches and therapies available for children, young people and adults on the autistic spectrum. This work offers concise and clear explanations of a variety of proposed interventions and their effectiveness, and helps the reader to decide on the most appropriate treatment for each individual. The author provides information about recent scientific evidence and the latest research, and allows the reader to consider the pros and cons of each approach. She focuses on the following areas: cognitive-behavioral approaches; developing social interaction; alternative communication strategies; developing play; sensory-motor approaches; psychotherapeutic approaches; biochemical approaches. This guide for practitioners and student teachers provides a comparative examination of the variety of treatments on offer.
'Greek edition first published 2005'--T.p. verso.
Includes bibliographical references (p. 143-180) and index.
Keywords: Autism in children -- Treatment; Austistic children -- Education; Autism spectrum disorder in children